Pengaruh Media Audio Visual Terhadap Perkembangan Kognitif Anak Kelompok B Di Tk Pertiwi Jenggrik IISragen Tahun Ajaran 2016/2017. - Pambudi, Pangestika Arum; , Dra. Surtikanti, S.H.,M.Pd (2017)
The purpose of this study to determine the influence of audio visual media on the cognitive development of children group B in TK Pertiwi Jenggrik II academic year 2016/2017. This study uses Experimental Pre Design (Pre-Experimental Designs) with One-Group Pretest-Posttest Design as a esearch design. This research was conducted in TK Pertiwi Jenggrik II Sragen. Subjects in this study are group B TK Pertiwi Jenggrik II Sragen with the number of 19 children. Technique of collecting data from this research is nonparticipan observation, data analysis technique in this research ttes with help of program SPSS 16.0 for windows. The result of data analysis using ttest obtained t count 18.237 < ttabel 1.734. Then Ho is rejected and Ha accepted which means there is influence of audio visual media on child cognitive development in child group B in TK Pertiwi Jenggrik II Kedawung District Sragen Regency.Keywords: audio visual, cognitive development